SYNTHESIS AND CHARACTERIZATIONS OF ZIRCONIA NANOCRYSTALLINE AND THIN-FILM FROM ZRCL4 THROUGH SOL-GEL METHOD - Hafizan Resha, Ahlul
Nanocrystalline zirconia has been successfully synthesized with 9-26 nm crystallite size from ZrCl4 as precursor through sol-gel method. Effects of precursor temperature, solvent composition, pH hydrolysis, and calcination temperature of the nano-zirconia phase was observed. According to TGA and XRD results, optimum condition for the formation of tetragonal phase is conducted through not-chilled precursors, the volume ratio of ethanol:water = 5: 1, pH hydrolysis is 9, and calcination temperature at 400 °C. Zirconia thin film has been fabricated through spin coating deposition technique by performing a variation of the sol concentration, spinning speed, and playback duration. Solid zirconia films obtained from the sol with a concentration of 0.2 M were rotated at a speed of 1200 rpm for 30 seconds. Nano- zirconia has a wide band gap at 5.10 to 5.17 eV with photoluminescence properties ?emission observed at 362 nm and 420 nm with ?excitation 265-325 nm and 440 nm ?emission also observed with broad peak and high intensity with ?excitation 354 nm. Zirconia thin film has a wide band gap at 3.4 eV and 4.6 eV with photoluminescence properties observed at ?emission 362 nm with ?excitation 265-340 nm, was measured by UV-Vis DRS and photoluminescence spectrophotometry. Therefore, thin film and nanocrystal of zirconia have potential as optoelectronic material.